The Welfare Effects of Extreme Weather Events : Insights from Three APEC Case Studies - World Bank (Washington, DC, 2013)
This report uses new measures of extreme weather and methodologies to gauge their welfare effects. A myriad of methodological issues and data constraints plague empirical work on the effects of extreme weather events on human welfare. The shocks themselves are often poorly measured and the lack of sufficiently long panel data or historical data on past events often forces a focus on effects in the short run. Economy wide effects of local shocks are typically only explored within the context of computable general equilibrium models which are very structural in nature. Proper evaluation of public interventions requires correction for the unobserved characteristics of the areas which receive the programs. The overall study was organized in four pillars: 1) fiscal options to address climate change; 2) technological options and role of trade and investment policies in fostering them; 3) capacity needs assessments; and 4) the human welfare effects of extreme weather events. To enable more in depth understanding of the methodologies used and the country specific insights emerging, the background papers underpinning each of the four pillars have been compiled in separate reports. This report provides an in-depth review of the empirical findings emanating from three country case studies examining the welfare effects of extreme weather. It concerns the occurrence of droughts in Indonesia, rainfall and temperature volatility in Mexico and droughts, floods and hurricanes in Vietnam.